2016
DOI: 10.1212/wnl.0000000000002362
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensity patterns in cerebral amyloid angiopathy and hypertensive arteriopathy

Abstract: Different patterns of subcortical leukoaraiosis visually identified on MRI might provide insights into the dominant underlying microangiopathy type as well as mechanisms of tissue injury in patients with ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
202
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 183 publications
(209 citation statements)
references
References 32 publications
4
202
1
2
Order By: Relevance
“…Patients with CAA had higher CMB counts, as in previous studies (p , 0.001). 6,23 No adverse event from any of the study procedures was observed in any participant.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Patients with CAA had higher CMB counts, as in previous studies (p , 0.001). 6,23 No adverse event from any of the study procedures was observed in any participant.…”
Section: Resultsmentioning
confidence: 93%
“…19,20 In our largest analyzed series of consecutive primary ICH patients who had MRI (n 5 526), patients with uncertain diagnoses were common (isolated lobar ICH, n 5 122, 23.2%; mixed location or cerebellar ICH, n 5 76, 14.5%) relative to the more definite diagnostic categories (probable CAA, n 5 191, 36.3%; HTN-ICH, n 5 137, 26%). 6 Older patients with multiple lobar microbleeds without ICH (lobar microbleed-only patients) show clinical, radiologic, and risk factor profiles of CAA, 26 but low microbleed counts on MRI are associated with a decreased probability of confirming CAA on autopsy. 34 These data suggest that for more than one third of primary ICH patients and for lobar microbleed-only patients with low microbleed burden, adjunctive diagnostic methods are needed for establishing the diagnosis of CAA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain MRI before LAA may be helpful for selecting patients at higher risk of further bleeding after brain hemorrhage [14] as the presence of cerebral CMBs and severe LA are recognized as markers of bleeding risk [16][17][18].…”
Section: Discussionmentioning
confidence: 99%